Hubungan Pengetahuan Ibu Dengan Pemanfaatan Buku Kesehatan Ibu dan Anak di Wilayah Kerja Puskesmas Martapura 2 - Rahmah, Nadia Rahima; Hipni, Rubiati; Setiawati, Erni; Kirana, Rita (JURNAL KEBIDANAN BESTARI, 2024)
In the Maternal and Child Health Book (KIA) there is information about pregnancy, the postpartum period, newborns and danger signs, instructions on maternal and infant nutrition, as well as a card to health. Pregnant mothers in the Martapura 2 work area who are less active in accessing information about maternal and child health books (KIA) will have an impact on the mother's insight being less and the impact being that she will not understand the importance of maternal and child health books (KIA). The research used was quantitative with a descriptive analytical cross sectional approach. The population in this study were mothers who attended classes for pregnant women in the working area of Martapura 2 Community Health Center, using the Accidental Sampling technique. Data collection uses a questionnaire. Data were analyzed using the chi square test. The results of the chi-square statistical test between the knowledge variable and the use of maternal and child health books (KIA) showed a p-value of 0.007< α. Conclusion: There is a relationship between maternal knowledge and the use of maternal and child health (KIA) books for pregnant women.Keywords: Knowledge, use of maternal and child health (KIA) books, pregnant women